JFQ volume 25 issue 3 Cover and Front matter (Journal of Financial and Quantitative Analysis, 1990)
The JFQA publishes theoretical and empirical research in financial economics. Corporate finance, investments, capital and security markets, and quantitative methods of particular relevance